Principals and Partners: The Structure of Syndicates - Daniel R. Vincent (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper analyzes conditions, which help to determine the optimal organization of a syndicate when the input of members of the syndicate is not observable. If the cost of monitoring agents' actions is free or if a principal will agree to operate an optimal incentive scheme at no cost, then well-known results tell us that a principal-based hierarchy is optimal. However, when all members of a syndicate share equally in the surplus generated by the syndicate including the principal, this cost must be borne in mind in forming the optimal organization. Sometimes it is preferable to bear the costs of shirking rather than to share the gains of the enterprise with another agent. This paper shows that the bias towards such partnerships varies in a predictable manner determined by the parameters of the environment. In particular, it shows that while growth of an enterprise might provide an incentive to form a hierarchy, increased efficiency of the agents through learning for instance provide countering biases favouring the formation of a partnership.
Keywords: 330